Limitation of mouth opening after radiotherapy for head and neck - CAETANO,Rafael da Silva (2016)
ABSTRACT Objective: To evaluate the ability to open the mouth in patients undergoing radiotherapy for head and neck and the variables related to this limitation. Methods: 32 patients were evaluated six months after completion of radiotherapy sessions to treat cancer in the head and neck. The maximum mouth opening was measured using digital calipers and its association with gender, age, smoking, alcohol consumption, tumor location, chemotherapy and surgery were analyzed using the Mann-Whitney and Kruskal-Wallis tests at a level of significance of 95%. Results: The mean age of patients was 60.44 years; 87.5% were male; 81.2% were smokers; 65.6% regularly consumed alcohol. The average mouth opening was 43.17 mm and seven (21.9%) patients had trismus. The most common locations of the tumors were the tongue (31.3%) followed by the larynx and vocal folds with five (15.6%) each. No association was found between limited mouth opening and the other variables. Conclusion: In this sample, 21.9% of patients had trismus six months after completing radiotherapy. The variables gender, age, smoking habits and alcohol consumption, tumor location, previous surgery and adjunctive chemotherapy were not associated with limited mouth opening.